Two modes of out-of-classroom instructional strategy and youths' attitude to voter education programme in Ondo city (2022)
The study investigated two modes of out-of-classroom instructional strategies on youths' attitude to voter education programme in Ondo city. The study adopted the pretest-posttest control group quasi- experimental design. The multi-stage sampling procedure was adopted. Two Local Government Areas (LGAs) in Ondo City were enumerated. The random sampling technique was used to select four community-based fora (2 per LGA). Fifty youths were purposively selected. Instruments used were Attitude to Voter Education Programme Questionnaire (AVEPQ r =0.74); Interest in Politics Questionnaire (IPQ r= 0.87); Instructional Guide on Youths Ambassadorial Learning Instruction (IGYALI); Instructional Guide on Social Media Learning Instruction (IGSMLI), Instructional Guide on Conventional Voter Education Strategy (IGCLMS) and Research Assistant Evaluation Sheet (RAES). The data collected were analyzed using Inferential Statistics Analysis of Covariance (ANCOVA). Estimated Marginal Means (EMM) aspect of ANCOVA was used to determine the magnitude of the mean scores of the different groups. Finally, the Bonferoni post-hoc analysis was used to determine the source of observed significant differences. The age of the respondents was within 30.80 ±2.40) years. The findings show among others that that there is a significant main effect of treatment (Treatment, Interest in Politics and Gender) on students' attitude to voter education programme; Interest in politics had effect on youths' attitude voter education programme; Gender had no effect on youths' attitude to voter education programme. INEC should continue the deployment of youths' ambassadorial strategy in conveying voter education messages. Social media influencers should also be enlisted to advocate positive messages of voter education across the length and breadth of the country